Difficulties and success factors in the development and application of the professional project and personal brand: an evaluative study - Carrillo González, Fermín (Revista Complutense de Educación, 2024)
In today's labor market, which is characterized by uncertainty, complexity, and ambiguity, it is important for people to develop tools to effectively manage their careers. In this regard, a professional project and personal brand could help improve employment opportunities. This research aims at identifying the challenges and factors that contribute to success in developing and implementing a professional project and personal brand for a sample of 65 people in the fields of psychology and education who participated in a career guidance program to increase their employment opportunities. On a periodic basis and for a period of 6 months, they responded to follow-up questionnaires that asked them about the challenges they faced in developing and implementing their professional project, as well as the positive effects of its application. After validating and applying a system of categories, the results showed that the most difficult elements to develop in a professional project are the strategy, the SWOT analysis, and the action plan. The main barriers to its implementation are lack of time and circumstantial factors for each person. Regarding the elements that were identified as important and that had positive effects on the employability of the participants, they were the strategy, knowing how to promote oneself, networking, and taking action. Finally, 70.2% of the sample reported having received some job opportunity during the 6 months as a result of the application of the professional project. The results of this study indicate that developing a professional project and personal brand is a complex process, but it can have positive effects on employability. It is concluded that it is necessary to implement more innovative career guidance programs related to professional project management, personal branding processes, and entrepreneurship.
Keywords: personal Brand; employability; professional project; vocational guidance; entrepreneurship